The Symbolic and Cultural Meanings of Arabic Calligraphy and Islamic Ornaments in Relation to Function and Social Status in the Mamluk Era - Mohga Mohamed Fouad Mohamed; Hartono Hartono; Wahyu Lestari; Mohga Mohamed Fouad Mohamed; Hartono Hartono; Wahyu Lestari (Universitas Negeri Malang, 2026)
This study examines the symbolic and cultural meanings of Arabic calligraphy and Islamic ornamentation in the Mamluk period, with particular attention to their functional roles and relationship to social status across manuscripts and architectural contexts. Employing a qualitative, comparative visual analysis, the research investigates how script styles, ornamental systems, materials, and spatial placement operated as intentional communicative strategies rather than mere decorative elements. The findings demonstrate that calligraphy and ornamentation formed an integrated visual language that articulated religious authority, political legitimacy, and hierarchical social order. In manuscripts, refined scripts and illuminated compositions emphasized textual sanctity and elite patronage, while in architecture, monumental inscriptions and durable materials projected authority and collective identity within public space. The study further reveals that visual hierarchy was carefully calibrated to audience, medium, and function, enabling meaning to be transmitted beyond textual literacy. By foregrounding the relationship between form, function, and social context, this research contributes to a deeper understanding of Islamic applied arts as systems of cultural communication. The study offers a framework for interpreting Mamluk visual culture as a cohesive and purposeful design practice, with implications for heritage interpretation, arts education, and contemporary applications of Islamic visual principles in promoting cultural continuity and inclusive access to historical knowledge.